KEEFEKTIFAN MODEL PEMBELAJARAN TIME TOKEN TERHADAP KETERAMPILAN BERBICARA SISWA SMK XYZ PALEMBANG - Octarina, Ayu (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to determine the effectiveness of the Time Token learning model on the speaking skills of students at SMK XYZ Palembang. The research method used is a quasi-experimental study. The results showed that the average value of the initial test of the experimental class was 49.55 and the control class was 47.75, while the average value of the final test of the experimental class was 72.55 and the control class was 64.19. Thus, Ha which reads "There is a difference in speaking skills between students taught using the Time Token model and students taught using the conventional model (µ1 ≠ µ2)" is accepted. With the acceptance of Ha, it is concluded that the Time Token model is effective for the speaking skills of students at SMK XYZ Palembang.Keyword: Time Token; speaking skills. Abstrak: Penelitian ini bertujuan untuk mengetahui keefektifan model pembelajaran Time Token terhadap keterampilan berbicara siswa SMK XYZ Palembang. Metode penelitian yang digunakan adalah eksperimen semu. Hasil penelitian menunjukkan bahwa nilai rata-rata tes awal kelas eksperimen 49,55 dan kelas kontrol 47,75, sedangkan nilai rata-rata tes akhir kelas eksperimen 72,55 dan kelas kontrol 64,19. Dengan demikian, Ha yang berbunyi “Ada perbedaan keterampilan berbicara antara siswa yang diajar menggunakan model Time Token dengan siswa yang diajar menggunakan model konvensional (µ1 ≠ µ2)” diterima. Dengan diterimanya Ha, maka disimpulkan bahwa model Time Token efektif terhadap keterampilan berbicara siswa SMK XYZ Palembang.Kata kunci: Time Token; keterampilan berbicara.